2019
DOI: 10.1177/0004867419888027
|View full text |Cite
|
Sign up to set email alerts
|

Differential biomarker signatures in unipolar and bipolar depression: A machine learning approach

Abstract: Objective: This study used machine learning techniques combined with peripheral biomarker measurements to build signatures to help differentiating (1) patients with bipolar depression from patients with unipolar depression, and (2) patients with bipolar depression or unipolar depression from healthy controls. Methods: We assessed serum levels of interleukin-2, interleukin-4, interleukin-6, interleukin-10, tumor necrosis factor-α, interferon-γ, interleukin-17A, brain-derived neurotrophic factor, lipid peroxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…After remission of depression, patients with BD had elevated IL-4 and TNF [ 74 ]. Wollenhaupt-Aguiar et al (2020) showed that the most relevant predictor markers to differentiate bipolar from unipolar depression were IL-10, thiobarbituric acid reactive substances, and IL-4 [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…After remission of depression, patients with BD had elevated IL-4 and TNF [ 74 ]. Wollenhaupt-Aguiar et al (2020) showed that the most relevant predictor markers to differentiate bipolar from unipolar depression were IL-10, thiobarbituric acid reactive substances, and IL-4 [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a composite biomarker panel was able to discriminate between patients with rapid-cycling BD and healthy individuals and between manic and depressive states [22]. It was also shown that machine learning techniques, coupled with peripheral biomarkers, provided a potential diagnostic tool to aid in distinguishing depressed patients with BD from major depressive disorder [23]. The field has been investigating several biological pathways, mostly associated with inflammation, oxidative stress, neurotrophic factors, and cellular resilience.…”
Section: Figure 1 Neuroprogression In Bipolar Disorder (Bd) Associamentioning
confidence: 99%
“…In addition, patients with unipolar depression and healthy controls also showed an AUC of 0.74, with 0.69 sensitivity and 0.70 specificity using seven variables (IL-6, carbonyl, BDNF, IL-10, IL-17A, IL-4, and TNF-α). [94]. However, all the patients in this study were under medication, and drug-free patients were not included, although there is a possible association between peripheral markers and pharmacotherapy.…”
Section: Differentiation Of Unipolar Depressive Disorder From Bipolarmentioning
confidence: 99%
“…Although both BD and MDD are associated with an overall increase in cytokine and chemokine levels, these research findings show that BD and MDD patients have different immune profiles and that these profiles can be used for differential diagnosis with high accuracy. Poletti et al used a k-fold nested cross-validation procedure [95] when compared with the leave-one-out cross-validation in a previous study [94] to improve the model accuracy.…”
Section: Differentiation Of Unipolar Depressive Disorder From Bipolarmentioning
confidence: 99%